(untitled) (Colombia Medica, 2022)
Background: Tuberculin skin test (TST) has an important place in the diagnosis of , latent tuberculosis infection (LTBI) for nearly a century Objective: This study aimed to investigate the general characteristics of patients that were tested with TST in a university hospital within two years. Methods: Patients that were tested with TST were included study. The Mantoux method was used for the administration of TST. All patients were assessed with regards to LTBI. Results: A total of 661 patients, 345 (52.2%) men and 316 (47.8%) women, with a mean age of 43.0±15.9 years, were included in the study. Accordingly, TST was performed prior to anti-TNF biological agent therapy for 50% (331) of the participants, for LTBI screening before solid organ and/or hematological stem cell transplantation for 20.4% (135), for screening following contact with tuberculosis for 25.1% (166), for screening of healthcare professionals for 1.1% (7), and for medical report for 3.3% (22). 2.7% of the patients who took TST were diagnosed with active tuberculosis (14 with pulmonary tuberculosis and 4 with extrapulmonary tuberculosis). QuantiFERON-TB Gold (QFT) test was performed in 332 (50.2%) patients with anergic TST results. According to TST and QFT test results, 28.3% (187) of the patients were started on tuberculosis prophylaxis. Conclusion: While TST is most commonly performed for LTBI screening prior to biological agent therapy, almost one fourth of patients taking TST require tuberculosis prophylaxis. About half of the patients, on the other hand, require an additional QFT test.